Efficacy of thumbtack needle acupuncture combined with PCIA on patients after laparoscopic myomectomy: a randomized controlled trial - Mao, Peiyu; Meng, Weijie; Mao, Tongxin; Li, Hui; Xu, Xuqun; Jiang, Xuelu; Yang, Huadi (Frontiers in Medicine, 2024)
Background Pain and gastrointestinal dysfunction after laparoscopic myomectomy (LM) are crucial problems that obstruct it from becoming a “Day Surgery”. We assessed the effect and safety of thumbtack needle acupuncture (TNA) combined with patient-controlled intravenous analgesia (PCIA) for enhanced recovery after LM. Methods 52 patients were enrolled in the treatment group with TNA and the control group, respectively. Both groups received PCIA with no-background sufentanil. A bolus infusion of flurbiprofen axel of 50 mg or intravenous metoclopramide of 10 mg was given for rescue analgesia or antiemetic. The primary outcomes were visual analogue scale (VAS) scores at awakening, 36 h, 48 h and 60 h after LM. The secondary outcomes were VAS scores at 6 h, 12 h, 24 h and 72 h after LM, total amount of sufentanil consumed, number of requests for analgesic of PCIA (attempts), number of rescue flurbiprofen axel analgesia required, preoperative anxiety scores, gastrointestinal function recovery assessment, first ambulation time, length of hospital stay and patient satisfaction. Adverse events were also recorded. Results Compared with control group, the treatment group showed significantly lower VAS scores and fewer attempts, less total sufentanil consumption and a smaller number of rescue analgesia after LM, with lower preoperative anxiety scores and a higher satisfaction in pain management (P<0.05). Gastrointestinal function recovery was enhanced in the treatment group with earlier flatus and defecation, lower incidence of PONV and a smaller number of metoclopramide required (P<0.05). Ambulation was earlier and the length of hospital stay was shorter in the treatment group (P<0.05). No adverse event was observed in patients with TNA. Conclusions TNA is a safe intervention that can alleviate postoperative pain, decrease the total consumption of sufentanil, relieve preoperative anxiety, enhance the recovery of gastrointestinal function, and reduce the duration of hospitalization, making it an ideal adjunct treatment for postoperative recovery after LM. Further research is required to understand the mechanisms of this intervention.